Examining the Impediments Impacting the Employability of Office Administration Graduates within Legal Offices - Dulpina, Maria Theresa S.; Tumoling, Jered G.; Era, Gerald N.; Ramirez, Crisanto S. (The Indonesian Institute of Science and Technology Research, 2024)
This study investigates the impediments of office administration graduates seeking employment within legal offices, employing the descriptive survey method and utilizing statistical tools such as the weighted mean and ranking method. Data were collected from 50 graduates of Camarines Norte State College, as well as employers and stenographers from legal offices. The findings highlight a significant obstacle faced by office administration graduates: a lack of relevant internships and experience within legal settings, impeding their employment prospects within the legal sector. These results underscore the necessity for closer collaboration between academic institutions and legal offices to facilitate tailored internships and experiential learning opportunities. Additionally, integrating practical training modules into the curriculum is crucial to better prepare graduates for the demands of the legal profession. The implications of these findings extend to policymakers and educational stakeholders, emphasizing the importance of proactive measures to bridge the gap between academic training and industry requirements and enhance the employability of office administration graduates within legal offices.